THE ECONOMIC AND PSYCHO-SOCIAL EXPERIENCES AND COPING RESOURCES OF FAMILY MEMBERS CARING FOR PEOPLE LIVING WITH AIDS IN THEIR HOMES IN BHAMBAYI, KWAZULU-NATAL, SOUTH AFRICA - Raniga, Tanusha; Motloung, Siphiwe (Social Work/Maatskaplike Werk, 2014)
There is empirical evidence that families have responded with much resilience and compassion to caring for persons living with AIDS (PWAs) in their homes (Engelbrecht & Kasiram, 2007; Sekokotla & Mturi, 2004; Simpson & Raniga, 2004). At the same time families in poverty-stricken communities are increasingly struggling and failing to provide optimally for the economic and psycho-social needs of PWAs who are in their care (Bartlett & Finkbeiner, 2006; Darling, Olmstead & Tiggleman, 2009). It is not surprising, however, at a time when the devastating effects of HIV and AIDS are all too evident, that international organisations, national governments and civil society organisations recognise the invaluable role played by extended family members as support caregivers in the care of those terminally ill with AIDS.